The Nutritional Status of some Horticultural Crops in Salalah Region, Sultanate of Oman - M.M. El-Fouly (Journal of Agricultural and Marine Sciences, 1999)
A field survey has been conducted in Salalah region, Sultanate of Oman to evaluate the nutrient status of some horticultural crops and the respective soils. Soil and leaf samples were collected and analyzed. Soils were found to be characterized by high pH, high CaCO3 content, low or very low micronutrient contents. The unfavorable conditions caused nutrient deficiencies within the plant tissues. To correct the situation, fertilizer use should be based on soil testing and plant analysis, as well as information on farming system and farm management. Use of micronutrient fertilizers should be considered as a part of the fertilizer regime.